The Relationship Between Emotional Intelligence and Communication Anxiety in Adolescents - Oktaviani Oktaviani; Ardimen Ardimen; Desmita Desmita; Rafsel Tasadi (International Journal of Research in Counseling, 2022)
Communication anxiety often occurs among society, especially in adolescents which is indicated by communication disorders such as feeling uncomfortable when communicating such as feeling afraid and anxious, avoidance in communicating, withdrawal and excessive communication so that they only care about the quantity of communication quality, therefore emotional intelligence is needed to reduce the effects of communication anxiety felt by adolescents. The purpose of this study was to determine the correlation between emotional intelligence and communication anxiety in adolescents. The research method used is a quantitative method with a correlational type of research. The subjects were juveniles with a population of 115 adolescents. The data analysis technique is the Product Moment correlation test. The sampling technique used the method of taking 10% of the population, namely 53 adolescents. Researchers used the likert scale to obtain needed data on emotional intelligence and communication anxiety. The results of the study found that there was a significant relationship between emotional intelligence and communication anxiety in adolescents. This is evidenced by the correlation test results of 0.685 and the r-table value of 0.276. Thus, it can be concluded that the alternative hypothesis (Ha) is accepted and the nilil hypothesis (H0) is rejected. This means that emotional intelligence has a significant relationship with communication anxiety.